The Role of Housing Policy and Access to Health Services in Reducing Economic Inequality and Improving Welfare in Indonesia - Loso Judijanto; Rival Pahrijal; Muhamad Ammar Muhtadi (West Science Social and Humanities Studies, 2024)
This study investigates the role of housing policy and access to health services in reducing economic inequality and improving welfare in Indonesia. Using a quantitative approach, data were collected from respondents through a structured questionnaire employing a Likert scale. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The findings reveal that all hypothesized relationships are positive and significant. Specifically, access to health services significantly enhances welfare and reduces economic inequality. Similarly, housing policy significantly improves welfare and reduces economic inequality. These results underscore the critical impact of robust housing policies and accessible health services on achieving greater economic equity and enhanced overall welfare. The study provides essential insights for policymakers to design effective interventions aimed at fostering a more equitable and prosperous society in Indonesia.